2019
DOI: 10.3389/fenvs.2018.00159
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Phosphate Uptake in Arbuscular Mycorrhizal Roots Under Field Conditions

Abstract: Many crops are colonized with arbuscular mycorrhizal fungi (AMF), which can efficiently absorb nutrients such as phosphate from the soil. The utilization of mycorrhizal symbioses is one of the most promising options for developing resource-saving and sustainable agricultural systems. Most laboratory studies have illustrated the roles of AM symbiosis by inoculating plants with limited AMF isolates. In the field, however, the roots of crops are co-colonized with multiple AMF species, which are difficult to separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 145 publications
(184 reference statements)
3
45
1
1
Order By: Relevance
“…On the other hand, CT soils had more homogenized P levels throughout the tilled layer. The low P availability to plant roots in NT systems might have promoted the establishment of symbiotic relationships including those with mycorrhizae fungi, especially that these fungi are known to efficiently absorb phosphates from the soil (Kobae, 2019). This is reflected in our data, where a higher prevalence of mycorrhizae fungi was associated with NT ( Figure 4A).…”
Section: Discussionmentioning
confidence: 63%
“…On the other hand, CT soils had more homogenized P levels throughout the tilled layer. The low P availability to plant roots in NT systems might have promoted the establishment of symbiotic relationships including those with mycorrhizae fungi, especially that these fungi are known to efficiently absorb phosphates from the soil (Kobae, 2019). This is reflected in our data, where a higher prevalence of mycorrhizae fungi was associated with NT ( Figure 4A).…”
Section: Discussionmentioning
confidence: 63%
“…It is also known that other practices and variables have direct effects on the performance of AMF in agricultural systems. Among them, variations in soil type, indigenous AMF community and diversity, environmental changes, crop species and cultivars, and cultivation management (VAn GEEL, 2016;HART et al, 2017;JACoBY et al, 2017;SAWERS et al, 2017;KOBAE, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Athar et al (2005) reported better nodulation and nitrogen fixation in legumes due to the phosphorus nutrition. Nitrogenase activity was enhanced due to the application of AM fungi was reported by Kobae (2019). By keeping the above points the present study was undertaken to evaluate the efficiency of tripartite association.…”
Section: Introductionmentioning
confidence: 82%